Analysis of solving methods and complexity of algorithmics problems in Lithuanian and Baltic Olympiads - Dagienė, Valentina; Skūpienė , Jūratė (Lietuvos matematikos rinkinys, 2003)
Lithuanian Olympiads in Informatics are being organized since 1990. Each Olympiad consists of three rounds. The final (national) one is divided into two parts, there are also elder and younger divisions. Each year there are supplied a lot of tasks. The paper deals with algorithmic problems of all the Lithuanian olympiads of school students and all the rounds from the point of view of their  methods of solution and complexity (from the student’s point of view).This kind of analysis will be useful for systematic developing of teaching programming and for the selecting problem set for the national Olympiads in the future.